HIV reverse transcriptase and protease genes variability can be a biomarker associated with HIV and hepatitis b or c coinfection - Cantão, Natália Mirele [UNESP]; Fogaça De Almeida, Lauana [UNESP]; Rodrigo Wolf, Ivan [UNESP]; Oliveira Almeida, Rodrigo [UNESP]; Alves De Almeida Cruz, Andressa [UNESP]; Nunes, Caroline [UNESP]; Barbosa, Alexandre Naime [UNESP]; Valente, Guilherme Targino [UNESP]; De Moura Campos Pardini, Maria Inês [UNESP]; Grotto, Rejane Maria Tommasini [UNESP] (Springer Nature, 2018)
Variability of the HIV reverse transcriptase (RT) and protease (PR) genes has been used as indicators of drug resistance and as a mean to evaluate phylogenetic relationships among circulating virus. However, these studies have been carried in HIV mono-infected populations. The goal of this study was to evaluate, for the first time, the HIV PR and RT sequences from HIV/HBV and HIV/HCV co-infected patients. HIV PR and RT genes were amplificated and sequenced to resistance analysis. The bioinformatics analysis was performed to infer about sequences clustering and molecular evolution. The results showed that the most frequent amino acid substitutions in RT were L214F (67.6%), I135T (55.9%), and in PR was V15I (41.2%). The molecular clock analysis showed that the HIV circulating in co-infected patients were separated in two clusters in the years 1999-2000. Some patients included as HIV mono-infected according patients' medical records and inside the co-infected cluster were, in fact, co-infected by PCR analysis. Analysis of the decision trees showed susceptibility to lamivudine and emtricitabine were important attribute to characterize co-infected patients. In conclusion, the results obtained in this study suggest, for the first time, that HIV RT and PR genes variability could be a genetic biomarker to coinfection.